(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Mandibular third molar presence and position may have an effect on the risk of mandibular angle fracture. Objective: The purpose of the present study was to see the effect of mandibular third molar presence and position on the risk of mandibular angle fracture. Methodology: This cross-sectional study was conducted in four centers in Bangladesh from July 2009 to June 2010 for a period of one year. The mandibular angle fractured patients were selected for the study. The medical records and panoramic radiographs of patients with mandibular angle fracture were examined. The presence or absence and degree of impaction of the mandibular third molars were assessed for each patient and related to the occurrence of fracture of the mandibular angle. Data were also collected for age, sex, mechanism of injury, number and location of mandibular angle fractures. Results: A total number of 100 patients with mandibular angle fracture were analyzed. The mean age is 44.36±21.9 years. Among 100 cases, 75 cases had lower third molars and 25 cases had without lower third molars. Within the 75 patients, 64 cases had impacted third molars while 11 cases had erupted third molars. Among the impacted group, 64.1% cases were mesioangular, 15.6% cases were horizontal, 12.5% cases were distoangular and 7.8% cases were vertical. Conclusion: In conclusion mandibular angle that contains an impacted lower third molar is more susceptible to fracture when exposed to trauma than an angle without lower third molar. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):181-184